THE ABILITY OF COFFEE AGROFORESTRY SYSTEM TO STORE CARBON STOCK - Fahriza Luth; Hadi Setiyono (Faculty of Forestry and Environment, Universitas Kuningan, 2018)
Each type of forest ecosystem and the species in it have different abilities to absorb CO2 and produce biomass. Coffee-based agroforestry is thought to be able to increase the ability of forests to store carbon as a result of increasing species composition and density of plants in these forest areas. This study aims to determine the composition of plants and carbon stocks stored in coffee-based agroforestry forests in LMDH Paniis RPH Rancakalong BKPH East Manglayang KPH Sumedang Perum Perhutani Regional Division West Java and Banten. This study uses survey and experiment methods. Data obtained through observations in the field and laboratory are in the form of tree names, wood density, tree biomass and carbon stocks from biomass. The result shows that the agroforestry forest composition at LMDH Paniis RPH Rancakalong BKPH East Manglayang KPH Sumedang within 17,14 ha consists of Pine (Pinus mercusii), Big-leaf Mahogany (Swietenia macrophylla), Clove (Syzygium aromaticum) dan Coffee (Coffea arabica). The carbon stock is 1.869,73 kg/ha in agroforestry forest, 2.618,32 kg/ha in primary natural forest, and 1.460,91 kg/ha in secondary natural forest. Agroforestry forest has more carbon stock than secondary natural forest does and agroforestry forest has less carbon stock than the primary natural forest